First‐in‐human phase 1 study of MK‐1248, an anti–glucocorticoid‐induced tumor necrosis factor receptor agonist monoclonal antibody, as monotherapy or with pembrolizumab in patients with advanced solid tumors. Issue 22 (18th August 2020) - Geva, Ravit; Voskoboynik, Mark; Dobrenkov, Konstantin; Mayawala, Kapil; Gwo, Jennifer; Wnek, Richard; Chartash, Elliot; Long, Georgina V.
Abstract : Background: Ligation of glucocorticoid‐induced tumor necrosis factor receptor (GITR) decreases regulatory T cell–mediated suppression and enhances T‐cell proliferation, effector function, and survival. MK‐1248 is a humanized immunoglobulin G4 anti‐GITR monoclonal antibody agonist. Methods: In patients with advanced solid tumors, MK‐1248 (starting dose, 0.12 mg) was tested alone and with pembrolizumab (200 mg) according to a 3 + 3 dose escalation design (ClinicalTrials.gov identifier NCT02553499); both treatments were administered intravenously every 3 weeks for ≤4 and ≤35 cycles, respectively. The safety and tolerability, maximum tolerated dose, and pharmacokinetics/pharmacodynamics were explored. Results: Twenty patients received MK‐1248 monotherapy; 17 received combination therapy. The most frequent tumor types were colorectal cancer (n = 8), melanoma (n = 6), and renal cell carcinoma (n = 4). MK‐1248 was generally well tolerated at the maximum tested doses of 170 (monotherapy) and 60 mg (combination). No dose‐limiting toxicities (DLTs) or treatment‐related deaths occurred. Adverse events (AEs) occurred in 36 of the 37 patients (97%); the most common were vomiting (n = 13 [35%]), anemia (n = 10 [27%]), and decreased appetite (n = 10 [27%]). Grade 3 to 5 AEs occurred in 19 of the 37 patients (51%). Treatment‐related AEs occurred in 18 of the 37 patients (49%): 9 of the 20 patients (45%) on monotherapy and 9 of the 17 patients (53%) on combination therapy. Among the 17 patients receiving combination therapy, 1 achieved a complete response and 2 achieved a partial response, for an objective response rate of 18%; no patients achieved an objective response with monotherapy. The disease control rate (stable disease or better) was 15% with monotherapy and 41% with combination therapy. Conclusions: MK‐1248 was generally well tolerated at doses up to 170 (monotherapy) and 60 mg (combination), with no DLTs or treatment‐related deaths. Combination therapy provided limited antitumor responses. Abstract : MK‐1248 has a manageable safety profile and limited antitumor activity when it is combined with pembrolizumab in patients with advanced solid tumors. The role of combination therapy with a glucocorticoid‐induced tumor necrosis factor receptor agonist and an immune checkpoint inhibitor still needs to be elucidated.